Side Effects of Phototherapy on Neonates - Faulhaber, Fabrízia R. S.; Procianoy, Renato S.; Silveira, Rita C. (American Journal of Perinatology, 2019)
Phototherapy in neonates for treatment of pathological jaundice is an effective therapeutic tool that is widely used in neonatal units. Over the past years, a greater concern has emerged about the effects on the immune and inflammatory system and its potential genotoxic and side effects, especially the late ones, possibly associated with childhood diseases, showing that this treatment is not as harmless as previously believed. Numerous studies assessing these possible adverse effects of phototherapy on neonates have been published over the past years. Through this review, we seek to analyze what we know about the side effects of phototherapy in the neonatal period. The main causes of jaundice, phototherapy techniques, acute and late side effects, and effects on the immune and inflammatory system were reviewed. It was concluded that phototherapy is not a treatment free of side effects and further studies need to be conducted to elucidate its harmful effects on neonates.
Keywords: jaundice; hyperbilirubinemia; neonate; phototherapy; side effects